2018
DOI: 10.1093/mnras/sty306
|View full text |Cite
|
Sign up to set email alerts
|

Mass ejection in failed supernovae: variation with stellar progenitor

Abstract: We study the ejection of mass during stellar core-collapse when the stalled shock does not revive and a black hole forms. Neutrino emission during the protoneutron star phase causes a decrease in the gravitational mass of the core, resulting in an outward going sound pulse that steepens into a shock as it travels out through the star. We explore the properties of this mass ejection mechanism over a range of stellar progenitors using spherically-symmetric, time-dependent hydrodynamic simulations that treat neut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 84 publications
13
154
0
Order By: Relevance
“…In Paper I, it was shown that the CQR self-similar solution very accurately reproduced the simulation results of Fernández et al (2018), who numerically studied the propagation of a weak shock through the envelope of a yellow supergiant (evolved from the zero-age main sequence with the stellar evolution code mesa; Paxton et al 2013Paxton et al , 2015Paxton et al , 2018 following its failure to explode in a traditional supernova. In their simulation, the shock was generated by the sudden decrease of the gravitational field that follows the formation of the proto-neutron star during core-collapse.…”
Section: Discussionmentioning
confidence: 80%
“…In Paper I, it was shown that the CQR self-similar solution very accurately reproduced the simulation results of Fernández et al (2018), who numerically studied the propagation of a weak shock through the envelope of a yellow supergiant (evolved from the zero-age main sequence with the stellar evolution code mesa; Paxton et al 2013Paxton et al , 2015Paxton et al , 2018 following its failure to explode in a traditional supernova. In their simulation, the shock was generated by the sudden decrease of the gravitational field that follows the formation of the proto-neutron star during core-collapse.…”
Section: Discussionmentioning
confidence: 80%
“…Alternatively, the intrinsic dipole mag- (2018); (4) Tauris et al (2015); (5) E.g. Miyaji et al (1980);Nomoto et al (1982); Moriya et al (2014) and references there in; (6) Fernández et al (2018); (7) Andrews & Smith (2018), Metzger & Pejcha (2017).…”
Section: Millisecond Magnetar From Successful Supernova With Low Ejecmentioning
confidence: 99%
“…Some studies (e.g. Nadezhin 1980;Lovegrove & Woosley 2013;Sukhbold et al 2016;Fernández et al 2018) stress that is quite unlikely that the H envelope collapses entirely, even during a direct collapse, because it is loosely bound. In the following, we consider the two extreme cases in which f H = 0 (the H envelope is completely lost) and f H = 0.9 (90 % of the H envelope collapses).…”
Section: Compactness Modelmentioning
confidence: 99%